PERANCANGAN DAN ANALISIS BIAYA-MANFAAT SISTEM SUPPLIER RELATIONSHIP MANAGEMENT (SRM) DI JOINT OPERATING BODY (J.O.B) PERTAMINA-PETROCHINA EAST JAVA - Hadi Siswidiastono; Joko Lianto Buliali (Jurnal Teknobisnis, 2005)
As a company which has always collaborate with suppliers, JOB Pertamina-PetroChina is well aware of the importance of suppliers’ role to support the company business process, which places them as a major force that need to be considered to achieve competitive advantages. Supplier satisfaction and loyalty supported by supplier performance evaluation is several important elements to support company’s business existence.In order to keep good relationship with suppliers, company faces several problems. Currently, there is no system available to manage suppliers’ database and its procurement. The purpose of this thesis is to design a Supplier Relationship Management for JOB P-PEJ followed by cost-benefit analysis. This new system is expected to help company to manage their supplier better in the future.The outcome expected from this study is a design of Supplier Relationship Management for JOB P-PEJ that is capable to determine most profitable supplier, to identify suppliers, and to manage complaints. Cost-benefit analysis will be done to evaluate whether the new system is useful to support Material and Logistic functions in managing suppliers.